Fatal Severe Community-Acquired Pneumonia with Sputum Retention in a 19-Year-Old Woman with Post-Poliomyelitis Syndrome: A Case Report - Thanisya Nabila Muthiarifa; Adhika Rahman (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Post-poliomyelitis syndrome (PPS) is a late complication of paralytic poliomyelitis in which progressive failure of enlarged motor units extends to the respiratory muscles, eroding ventilatory reserve and the capacity to clear airway secretions. Fatal pneumonia in a young adult with PPS is rarely documented. Objective: To describe a fatal case of severe community-acquired pneumonia in a young adult with PPS and to highlight the role of diminished respiratory reserve and sputum retention. Case presentation: A 19-year-old Indonesian woman with childhood paralytic poliomyelitis, generalized atrophy, thoracolumbar scoliosis, and pectus carinatum presented with one hour of acute dyspnoea preceded by three days of productive cough and fever. She was febrile (38.8°C), tachypnoeic and hypoxaemic (PaO₂ 58 mmHg; SpO₂ 93% on room air), with bilateral crackles, severe leukocytosis (30,100/µL), mild anaemia (9.0 g/dL) and Gram-positive cocci on sputum microscopy. Despite empirical antibiotics, bronchodilators, mucolytics, fluids and oxygen, she deteriorated within 24 hours, requiring intubation and mechanical ventilation; repeat blood gas showed profound metabolic acidosis (pH 6.914, base excess −26.5 mmol/L). She developed vasopressor-dependent septic shock with multi-organ failure and died on the sixth hospital day. Conclusion: The diminished respiratory reserve, ineffective cough and impaired airway clearance intrinsic to PPS can convert an otherwise moderate community-acquired pneumonia into rapidly fatal respiratory failure and septic shock; such patients warrant early severity stratification, aggressive airway clearance and a low threshold for ventilatory support.